Safety and feasibility of contrast echocardiography for the evaluation of patients with HeartMate 3 left ventricular assist devices. (26th July 2017) - Schinkel, Arend F L; Akin, Sakir; Strachinaru, Mihai; Muslem, Rahatullah; Soliman, Osama I I; Brugts, Jasper J; Constantinescu, Alina A; Manintveld, Olivier C; Caliskan, Kadir
Abstract: Aims: Patients with a left ventricular assist device (LVAD) are challenging to evaluate using conventional imaging techniques, such as standard echocardiography (SE). The aim of this pilot study was to evaluate the potential of contrast echocardiography (CE) for the evaluation of the left ventricle (LV). Methods and results: This prospective study included 14 ambulatory patients (mean age 58 ± 9 years, 79% male) with a LVAD (all HeartMate 3, Abbott Laboratories, Chicago, IL, USA). Nine (64%) patients had an ischaemic cardiomyopathy, and 5 (36%) had a non-ischaemic cardiomyopathy. All patients underwent SE and CE using intravenous administration of Sonovue contrast agent (Bracco, Milan, Italy). The echocardiograms were assessed by three observers, using a standard 17-segment model of the LV. Left ventricular end-diastolic volume (LVEDV) was assessed using the biplane Simpson method. The contrast agent was well tolerated by all patients, without any side effects. Overall, SE allowed visualization of 57% of LV segments (135/238) and CE allowed visualization of 79% of LV segments (187/238), P  < 0.001. Per patient, SE resulted in visualization of 9.6 ± 5.2 segments and CE was able to visualize 13.4 ± 5.8 segments ( P  < 0.001). Administration of contrast agent significantly improved the assessment of LVEDV (feasibility SE: 36% vs. CE: 79%, P  < 0.05). Conclusion: Routine use of a contrast agent appears safe when used in patients having a new third generation LVAD and may enhance the diagnostic accuracy of transthoracic echocardiography in these patients. LV size determination can be obtained more often due to improved LV visualization using contrast agent.